Citotoxicity and immune response induced by organopalladium(II) compounds in mice bearing Ehrlich ascites tumour - Rocha, Michelle C. da [UNESP]; Santana, Anderson M. [UNESP]; Ananias, Sandra R. [UNESP]; Almeida, Eduardo T. de; Mauro, Antonio Eduardo [UNESP]; Placeres, Marisa C. P. [UNESP]; Carlos, Iracilda Z. [UNESP] (FapUNIFESP (SciELO), 2007)
Cyclometallated palladium(II) complexes are reactive inorganic compounds employed in several biological studies because of their antitumour potential and interaction with immune system. In the present study, the immune and citotoxic response induced by two organopalladated complexes: [{Pd(N,C-dmba)} 2(μ-NCS) 2] (1), [Pd(C-dmba)(NCS)(dppp)] (2) [dmba = N,N′-dimethylbenzylamine, dppp = 1,3-bis(diphenylphosphino)propane] and cisplatin (cis-DDP), as standard, were investigated in mice bearing Ehrlich ascites tumour. The mice were divided into five groups and inoculated with the compounds (1) or (2) or cisplatin, or only vehicle or phosphate-buffered saline (PBS). Many parameters were evaluated, such as tumour cell percentage in the peritoneal exsudate, levels of seric nitric oxide (NO) and tumour necrosis factor-alpha (TNF-α) and increase in life span. Analysis of all data revealed, for compound (2), an activity similar to that presented by cisplatin, resulting in increased life span, lower levels of seric TNF-α and increase in NO production. ©2007 Sociedade Brasileira de Química.
Keywords: Ehrlich ascites tumour; Macrophages; Nitric oxide; Palladium(II) complexes; Tumour necrosis factor-alpha